The Effectiveness Of Senduduk Fruit Paste (Melastoma Malabathricum L.) On The Colonization Of Plaque-Forming Bacteria - Marlindayanti, Marlindayanti; Hanum, Nur Adiba; Aulia, Dias Mita (Journal Dental Health, 2023)
Background: The cause of dental and oral disease is plaque. Plaque is formed due to bacteria, such as Staphylococcus aureus, Pseudomonas aeruginoda and Escherichia coli. Plaque formation can be controlled by mechanical and chemical means. To control the formation of plaque can be done by using natural ingredients that contain antibacterial, one of the plants that contain antibacterial is senduduk fruit (Melastoma Malabathricum L.) This plant contains saponins, flavonoids and tannins which are chemical compounds and have potential as antibacterials. Objective: To determine the effectiveness of senduduk fruit paste (Melastoma Malabathricum L.) against plaque-forming bacteria colonization. Method: This study uses a true experiment with a pre and post-test control group design, In this study, the number of samples was calculated using the Federer formula and randomly selected. Data analysis using Two Way Anova. Results: Based on the treatment group the value is 0.000 <0.050. So it was concluded based on the treatment group had a significant effect on the number of results. Based on the time group value 0.248> 0.050. So it was concluded based on the time group did not have a significant effect on the number of results. Based on the treatment group and time (simultaneous/ together) the Sig value is 0.000 <0.050. So it can be concluded based on the time treatment group has a significant effect on the total results. Conclusion: senduduk fruit paste (Melastoma Malabathricum L.